Implementation of Human Resource Management in Enhancing Teacher Performance at Phatnawitya School, Yala, Thailand - Ady, Syifa Salsabilla Frisca; Hasanah, Uswah (Newinera Publisher, 2025)
This study aims to examine the implementation of Human Resource Management (HRM) in enhancing teacher performance at Phatnawitya School, Yala, Thailand, as well as to identify the obstacles faced in this process. A qualitative research approach was employed to gain an in-depth understanding of HRM implementation in the school setting. The findings reveal that HRM practices at Phatnawitya School have been effectively carried out, as evidenced by structured human resource planning, recruitment of qualified professionals, a systematic selection process, and job placements that align with school needs and teacher competencies. Additionally, the implementation of planned training programs and comprehensive performance evaluations contributes to overall improvement in teacher performance. Despite these strengths, several challenges persist, particularly regarding punctuality in morning attendance. Delays in teacher attendance negatively impact instructional time, reducing opportunities for both in-class and extracurricular learning. This issue presents a significant barrier to maximizing students’ knowledge acquisition. Addressing these obstacles through enhanced HRM strategies is essential to ensuring optimal teacher performance and educational outcomes at Phatnawitya School.